Visualization of focal sites of transcription within human nuclei. - Jackson, D; Hassan, A; Errington, R; Cook, P (1993)
HeLa cells were encapsulated in agarose microbeads, permeabilized and incubated with Br-UTP in a 'physiological' buffer; then sites of RNA synthesis were immunolabelled using an antibody that reacts with Br-RNA. After extending nascent RNA chains by < 400 nucleotides in vitro, approximately 300-500 focal synthetic sites can be seen in each nucleus by fluorescence microscopy. Most foci also contain a component of the splicing apparatus detected by an anti-Sm antibody. alpha-amanitin, an inhibitor of RNA polymerase II, prevents incorporation into these foci; then, using a slightly higher salt concentration, approximately 25 nucleolar foci became clearly visible. Both nucleolar and extra-nucleolar foci remain after nucleolytic removal of approximately 90% chromatin. An underlying structure probably organizes groups of transcription units into 'factories' where transcripts are both synthesized and processed.